2014
DOI: 10.1088/2041-8205/783/1/l14
|View full text |Cite
|
Sign up to set email alerts
|

A SUBSTANTIAL POPULATION OF MASSIVE QUIESCENT GALAXIES AT z ∼ 4 FROM ZFOURGE

Abstract: We report the likely identification of a substantial population of massive M ∼ 10 11 M galaxies at z ∼ 4 with suppressed star formation rates (SFRs), selected on rest-frame optical to near-IR colors from the FourStar Galaxy Evolution Survey (ZFOURGE). The observed spectral energy distributions show pronounced breaks, sampled by a set of near-IR medium-bandwidth filters, resulting in tightly constrained photometric redshifts. Fitting stellar population models suggests large Balmer/4000 Å breaks, relatively old … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
287
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(323 citation statements)
references
References 50 publications
30
287
6
Order By: Relevance
“…that are faint in the UV rest-frame but are bright in the IR bands, indicating that they are either highly obscured by dust or old/evolved objects, and thus they have large stellar masses. While the existence of passively evolved galaxies at z = 4 has also been shown recently by Straatman et al (2014) using the ZFOURGE data set and deep Herschel observations, in agreement with early results by Fontana et al (2009) in the GOODS-South field, we show here that they do contribute significantly to the high-mass end of the GSMF, certainly at z 4.…”
Section: Discussionsupporting
confidence: 93%
“…that are faint in the UV rest-frame but are bright in the IR bands, indicating that they are either highly obscured by dust or old/evolved objects, and thus they have large stellar masses. While the existence of passively evolved galaxies at z = 4 has also been shown recently by Straatman et al (2014) using the ZFOURGE data set and deep Herschel observations, in agreement with early results by Fontana et al (2009) in the GOODS-South field, we show here that they do contribute significantly to the high-mass end of the GSMF, certainly at z 4.…”
Section: Discussionsupporting
confidence: 93%
“…Galaxy ages are challenging to constrain observationally, due to the degeneracy between dust extinction, age and metallicity in spectral energy distribution (SED) fitting, which are especially severe at z ∼ > 4 where HST covers only the restframe UV wavelengths. Our modeling results are consistent with the picture emerging from multiple recent studies that combine HST and Spitzer/IRAC data and find that the majority of z ∼ > 4 galaxies to have old stellar populations (> 100 Myr) and relatively low specific SFR (∼ 100 M yr −1 ) (Oesch et al 2013a;Straatman et al 2014; see also González et al 2011 for earlier studies reaching the same conclusion but without accounting for nebular emission lines). However, other independent studies based mostly on overlapping datasets reached the different conclusion that z ∼ > 4 galaxies have a high chance of being young systems (ages < 50 Myr) with high specific SFRs (de Barros et al 2014;Finkelstein et al 2015a), suggesting that improved observational constraints are needed to evaluate the fidelity of stellar ages predicted by our model.…”
Section: Stellar Masses and Agessupporting
confidence: 90%
“…This value is much lower than that of the observed density claimed by Straatman et al (2014), ∼ 1 × 10 −6 Mpc −3 . However, we argue below that the number density of the ZF analogues has large uncertainties both in the observation and theoretical models.…”
Section: Discussion a N D S U M M A Rycontrasting
confidence: 58%
“…As the quite rare objects, the clustering of the massive QGs is indeed strong at z > 3, and therefore a much larger survey volume than ZFOURGE is needed to securely obtain the accurate observational number density. Secondly, SFR of the QGs given by Straatman et al (2014) may be underestimated; for instance, a part of ZF may be star forming and obscured by dust. Simpson et al (2017) argued that the strong Balmer features shown in ZF are not a unique signature of a poststarburst galaxy and are indeed frequently observed in infrared-luminous galaxies, and understanding high-redshift obscured starbursts will only be possible with multiwavelength and high-resolution observations.…”
Section: Discussion a N D S U M M A Rymentioning
confidence: 99%
See 1 more Smart Citation